THE IMPACT OF DOCKING KARADI LAMBS ON GROWTH PERFORMANCE, CARCASS TRAITS AND BODY COMPOSITION - Al-Sherwany, D. A. O.; Alkass, J. E. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Twelve new born Karadi lambs were docked within 3 days of their birth using rubber-rings, and left with their mothers till weaning (2.5 months). Another 12 weaned Karadi lambs obtained from local market were left intact. Following an adaptation period of a week, the docked and intact lambs with an average initial weight of 16.83±1.522 and 19.92± 0.748kg were randomly divided into three equal groups to be slaughtered at 20, 30 and 40kg. Results revealed that overall means of daily gain in weight, dressing percentage based on slaughter and empty body weight, rib eye area and fat thickness were 0.261±0.014kg, 45.956±0.428%, 53.933±0.678%, 11.288±0.488cm2 and 2.023±0.76mm, respectively, and no significant difference exist between them except dressing percentage based on empty body weight. It appears that carcasses of intact lambs compared to docked lambs contained significantly higher lean (62.79 vs. 59.85%), lean: fat (5.319 vs. 4.142), lean: bone (2.772 vs. 2.489) and numerically lower fat (16.058 vs. 14.042%) and bone (23.172 vs. 24.096%). Also, it was noticed as slaughter weight increase, there is an increase in dressing percentage, rib eye area, fat thickness, fat content of their carcass with a lower proportion of lean and bone.